Primary-side control for the flyback AC–DC converter - Zhang, Zhu; Ren, Mingyuan; Gao, Tianhang (Frontiers in Energy Research, 2023)
This paper proposes a PSR flyback switching power supply AC/DC control chip with a maximum rated power based on the SMIC 0.18 μm CMOS process. The flyback power management system based on pulse modulation technology working in the current discontinuous mode. The AC/DC control chip mainly includes power supply module, clock signal generation module, constant voltage control module, constant current control module, driving module, and constant voltage constant current mode switch module. The various module circuits of the system are analyzed and simulated. Compared with similar products, the system simulation results have advantages in some indicators.